2009
DOI: 10.1523/jneurosci.3155-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Feedback Induced by Front-Leg Stepping Entrains the Activity of Central Pattern Generators in Caudal Segments of the Stick Insect Walking System

Abstract: Legged locomotion results from a combination of central pattern generating network (CPG) activity and intralimb and interlimb sensory feedback. Data on the neural basis of interlimb coordination are very limited. We investigated here the influence of stepping in one leg on the activities of neighboring-leg thorax-coxa (TC) joint CPGs in the stick insect (Carausius morosus). We used a new approach combining single-leg stepping with pharmacological activation of segmental CPGs, sensory stimulation, and additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
157
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(179 citation statements)
references
References 54 publications
20
157
2
Order By: Relevance
“…At slower speeds, both juvenile and adult stick insects walked with a metachronal gait pattern. In a metachronal gait, a hindmost leg steps first, and each successive ipsilateral leg lifts off the ground immediately after its posterior neighbor touches down, suggesting that the legs are coordinated mainly by feedback (Borgmann et al, 2007;Borgmann et al, 2009). A mechanism for this was recently demonstrated in the cockroach P. americana by Zill and co-workers (Zill et al, 2010).…”
Section: Gait Controlmentioning
confidence: 92%
“…At slower speeds, both juvenile and adult stick insects walked with a metachronal gait pattern. In a metachronal gait, a hindmost leg steps first, and each successive ipsilateral leg lifts off the ground immediately after its posterior neighbor touches down, suggesting that the legs are coordinated mainly by feedback (Borgmann et al, 2007;Borgmann et al, 2009). A mechanism for this was recently demonstrated in the cockroach P. americana by Zill and co-workers (Zill et al, 2010).…”
Section: Gait Controlmentioning
confidence: 92%
“…In insects, both temporal and spatial co-ordination among legs is known to depend on sensory feedback (Wendler, 1964;Cruse, 1990;Ritzmann and Büschges, 2007), involving information about limb posture (Wong and Pearson, 1976;Cruse et al, 1984), load (Borgmann et al, 2009;Zill et al, 2009;Zill et al, 2012) and ground contact (Zill et al, 2010;Theunissen and Dürr, 2013). Thus the second objective of this study was to reveal the contribution of a proprioceptive hair field on the accuracy of spatial co-ordination between middle and hindlegs.…”
Section: Introductionmentioning
confidence: 98%
“…However, studies have shown the role of local sensory feedback in establishing inter-leg coordination, e.g. in the hawk moth (Johnston and Levine, 1996;Johnston and Levine, 2002) and the stick insect C. morosus (Borgmann et al, 2009;Büschges et al, 1995).…”
Section: Introductionmentioning
confidence: 99%